نعت گوئی: تعریف، اقسام، نعت کے اصول و آداب اور دیگر مباحث: Naat-gooi, definition types, principles and manners of Naat and other discussions - Dr. Hafiz Hamid Ali Awan,; Allah Bakhsh, (Al Manhal Research Journal, 2024)
It is a natural thing that when a person has affection, love and devotion to someone, he gets involved in his praise and praise. This is a requirement of humanity. When Allah, the Exalted, created the existence of His Beloved Imam of the Prophets, Sayyid Al- Mursaleen, the Holy Prophet (PBUH), first of all, he himself described the glory and praise of the Prophet (PBUH). Praise has been mentioned by Allah the Exalted in many places in the Holy Qur'an, Al- Muzmal , Al- Mudasir ,Yasin, in the most beautiful words such as Taha and Al- Zahi, Allah the Exalted addressed His Beloved Kabirya in an auspicious way. Allah the Exalted created this world and all the beautiful and attractive things in it only because of you (peace be upon him) and then he also praised his Beloved. In the follow- up, it describes the description and praise of the Prophet (peace be upon him). And this is praise is called Naat. Naat is an Arabic word that means praise and appreciation. In all the dictionaries of Urdu and Arabic, the word naat is used in the meaning of praise. Many intellectuals and scholars have recorded in their books that the creator of the word. The word Naat was first used by Hazrat Ali Karamullah Rabiyyah and after that the word Naat was used by Aqa. Two places are reserved for describing the glory and attributes of Prophet Muhammad (peace be upon him). The first Naat written is in Arabic language. Hazrat Hasan bin Thabit has the honor of being the first poet among the admirers of the Prophet, may God bless him and grant him peace. First of all, he described the greatness, virtues and praises of the Prophet (PBUH). After him, Hazrat Abbas bin Abdul Muttalib.